Antidepressant-like Responses to Lithium in Genetically Diverse Mouse Strains - Can, Adem (2011)
A mood stabilizing and antidepressant response to lithium is only found in a subgroup of bipolar disorder and depression patients. Identifying strains of mice that are responsive and non-responsive to lithium may elucidate genomic and other biological factors that play a role in lithium responsiveness. Mouse strains were tested in the forced swim, tail suspension, and open field tests after acute and chronic systemic, and intracerebroventricular and chronic lithium treatments. Serum and brain lithium levels were measured. Three (129S6/SvEvTac, C3H/HeNHsd, C57BL/6J) of the eight inbred strains tested, and one (CD-1) of the three outbred strains, showed an antidepressant-like response in the forced swim test following acute systemic administration of lithium. The three responsive inbred strains, as well as the DBA/2J strain, were also responsive in the forced swim test after chronic administration of lithium. However, in the tail suspension test, acute lithium resulted in an antidepressant-like effect only in C3H/HeNHsd mice. Only C57BL/6J and DBA/2J were responsive in the tail suspension test after chronic administration of lithium. Intracerebroventricular lithium administration resulted in a similar response profile in BALB/cJ (non-responsive) and C57BL/6J (responsive) strains. Serum and brain lithium concentrations demonstrated that behavioral results were not due to differential pharmacokinetics of lithium in individual strains, suggesting that genetic factors likely regulate responsiveness to lithium. Our results indicate that responsiveness to lithium in tests of antidepressant efficacy varies among genetically diverse mouse strains. These results will assist in identifying genomic factors associated with lithium responsiveness and the mechanisms of lithium action.